Pengaruh Edukasi Keuangan melalui Kebijakan Program Keuangan Inklusif terhadap Pencegahan Non Performing Loan pada Kredit Usaha Mikro di Kota Banda Aceh - Rita Nengsih; Zenitha Maulida; Ridha Ansari (Universitas Serambi Mekkah, 2017)
The objective of this research to describe how the financial education through inclusive program policy that developed by Bank Indonesia to the microfinance institution effected to prevent non performing loan (NPL) or usually mention as bad credit. The research did in formal microfinance institutions in Banda Aceh area, that focused on distribution micro credit to small business and did the financial education. The research data collected through primary data and secondary data. Primary data obtained from direct interview to micro credit bank staff and the secondary data obtained from the annual report bank in 2012 to 2014. Financial education to client is a part of services by micro finance institution. Financial education can prevent the small business from bankrupt and can be developed their business with the planning and a good financial management. The financial inclusive policy that developed by Bank Indonesia expected to decrease and prevent NPL. The result of the research showed that the overall NPL bank ratio in Banda Aceh area decreased every years. It means that the financial bank performances to decrease NPL micro credit are better. It can be concluded that the financial education on financial inclusive program did by bank to debtor affected to NPL micro credit ratio. In addition there are others factors outside the research influencing NPL micro credit ratio, such as government policy, Bank Indonesia policy and the economic condition of the country.